Genetic diversity and evolutionary relationships of the troglodytic 'living fossil'Congeria kusceri (Bivalvia: Dreissenidae) - Stepien, C. A.; Morton, B.; Dabrowska, K. A.; Guarnera, R. A.; Radja, T.; Radja, B. (Molecular Ecology, 2001)
Population genetic theory predicts that long‐term isolation of ‘living fossils’ in relic habitats might reduce genetic variability due to small population sizes and inbreeding. The recent description of a troglodytic ‘living fossil’Congeria kusceri — the only known subterranean bivalve mollusc — from a genus thought to be extinct since the Miocene, offers a unique opportunity to examine this hypothesis. Here, we use DNA sequences from two mitochondrial genes to compare levels of genetic variability and to test phylogenetic relationships of C. kusceri with surface‐dwelling dreissenid relatives. Phylogenetic analyses of sequences from the cytochrome oxidase 1 (COI) and 16S rDNA genes reveal that Mytilopsis is the sister genus to Congeria and this clade forms the sister taxon to Dreissena. Relatively high levels of DNA diversity characterized the population of C. kusceri (haplotypic diversity = 0.50 for 16S rDNA and 0.66 in the COI gene), in contrast to no intraspecific variability in populations of Dreissenapolymorpha, D. bugensis, Mytilopsisleucophaeta, and Corbiculafluminea. Maintenance of genetic variability in C. kusceri may result from long‐term population size stability, which merits further investigation. This underground species apparently was buffered from the climatic changes and resultant population bottlenecks that affected its surface‐dwelling relatives during the Pliocene and Pleistocene Ice Ages.